Territorial Marketing as a Method of Reduction of Outward Migration - Wawrzyniec Rudolf (Comparative Economic Research. Central and Eastern Europe, 2009)
The study considers problems of outward migration of the young population in regard to measures which should be taken by local governments in order to decrease this phenomenon. The author recommends here territorial marketing measures which may effectively restrain unfavorable tendencies. The study presents interesting example of marketing programme aimed at convincing young residents of Łod́zńot to leave cityafter graduation and to bind their future professional life with the place where they are studying and learning. The programme has been directed to acquire new students who in future may contribute to the increase of town's attractiveness and development. The first results of evaluation of the programme conducted in 2009 proved that the initiative has been well perceived and was quite popular. Whereas only its further development and stages that will follow will present the answer about its effectiveness.
Keywords: 330